"May I present you: my disgust!" – Declared disgust sensitivity in the presence of attractive models. - Stefanczyk, Michal Mikolaj; Lizak, Katarzyna; Kowal, Marta; Sorokowska, Agnieszka (British Journal of Psychology, 2022)
Disgust sensitivity differs among men and women, and this phenomenon has been observed across numerous cultures. It remains unknown why such sex differences occur, but one of the reasons may relate to differences in self‐presentation. We tested that hypothesis in an experiment comprising 299 participants (49% women) randomly allocated into three groups. Each group completed the Three Domains Disgust Scale (TDDS) and rated how disgusting they found olfactory, visual, gustatory, and tactile disgust elicitors either when a male experimenter was present, a female experimenter was present, or no experimenter was present. We hypothesised that male participants in the female experimenter group would declare decreased levels of disgust sensitivity, and female participants in the male experimenter group would declare increased levels of disgust sensitivity. Results showed that despite sex differences in pathogen and sexual disgust, attractive experimenters did not evoke any differences in declared disgust across groups with one exception–both men and women self‐presented as more sensitive to sexual disgust in the presence of the female experimenter. We discuss our findings in the light of evolutionary and social theories.